Prevalence of Nasopharyngeal Carcinoma among Patients with Nasopharyngeal Mass in a Philippine Tertiary Training Hospital - Hasmin Hannah R. Lara; Angelo A. Monroy (Philippine Journal of Otolaryngology Head and Neck Surgery, 2016)
Objectives: To determine the prevalence and identify the types of Nasopharyngeal Carcinoma (NPCA) among patients with nasopharyngeal mass seen at a tertiary university training hospital in the Philippines from January 2006 – July 2012 and identify possible factors associated with nasopharyngeal carcinoma.